Agitation in dementia and the role of spatial and sensory interventions: experiences of professional and family caregivers. Issue 2 (11th May 2015) - Van Vracem, Marieke; Spruytte, Nele; Declercq, Anja; Van Audenhove, Chantal
Abstract : Aim: There is a growing interest in environmental interventions to complement the psychosocial approaches to cope with agitation in dementia. The aim of this study was to present this evidence from literature and research to care practitioners and family carers in order to gather their reflections. In this way, we can identify experienced gaps in care practice and define needs for further research. Method: A framework with seven types of environmental interventions for agitation in dementia was developed through literature review, referring to the impact of light, smell, noise, temperature, nature, colour and spatial configuration. This framework guided three expert panels, respectively, with family caregivers of persons with dementia (N = 5), professional home care workers (N = 12) and professional caregivers working in nursing homes (N = 10). Results: All caregivers stressed the impact of agitation on their quality of life and on the quality of life of the person with dementia. Most caregivers were familiar with the impact of daylight, natural elements and domestic smells. Caregivers were unfamiliar with the specific effects of bright light therapy and were interested in more research on the effectiveness of light, temperature and spatial configuration. They stressed the individuality of agitation in dementia. Conclusion: Caregivers already use sensory and spatial interventions to manage agitation, and they are interested in knowing more about feasible effective interventions. Caregivers need to be informed on the possible benefits of sensory environmental factors on coping with agitation. To this end, it is very useful to take the experiences of caregivers into account.